Are start-ups ready to adopt a balanced scorecard? - Castro, Elisabete Andreia Pinto (2015)
Balanced Scorecard (the BSC) is recognized as one of the most powerful strategic management tools due to its ability to translate the long-term strategy into short-term goals and in financial and non-financial indicators. Considering the Portuguese business context in which the number of start-ups has increased significantly, this constitute a relevant study universe to relate the BSC with companies in the initial phase of the business life-cycle. For this, it was applied an interview to 9 start-ups to determine the level of willingness to adopt the BSC by considering their organizational characteristics. The main conclusion is that it seems to be a pattern that relates the business life-cycle stage in which a company is, with the willingness to adopt the BSC. Indeed, 8 over the 9 start-ups studied revealed not being willing to adopt the BSC in their companies due to their organizational characteristics that are inherent to the birth stage of the business life-cycle to which they belong and that constitute themselves obstacles to implement this tool. These start-ups attribute several advantages to the BSC by considering it is a very well designed tool but those are lessened by the obstacles found such as the scarcity of resources and the need to constantly change. Furthermore, the strategic management practices seem to be related to the willingness to adopt the BSC because this tool requires a long-term strategy and start-ups are short-term focused. To finalize, the willingness to adopt the BSC is higher from the birth stage to the growth stage as a result of the need to adapt internally to the increasing complexity of the company.